2015
DOI: 10.1371/journal.ppat.1005284
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Induces Cholesterol-Enriched Endocytic Recycling Compartments for Budozone Formation via Cell Cycle-Independent Centrosome Maturation

Abstract: Influenza virus particles are assembled at the plasma membrane in concert with incorporation of the virus genome, but the details of its spatio-temporal regulation are not understood. Here we showed that influenza virus infection induces the assembly of pericentrosomal endocytic recycling compartment (ERC) through the activation of Rab11a GTPase and cell cycle-independent maturation of centrosome by YB-1, a multifunctional protein that is involved in mitotic division, RNA metabolism and tumorigenesis. YB-1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 51 publications
1
54
1
Order By: Relevance
“…Although vesicular clustering might, at some level, be in agreement with the reduction of recycling endosome efficiency that we report here, the existence of vesicles with double membranes suggests a distinct mechanism to rearrange membranes that we have not addressed and might be related to lipid metabolism. Interestingly, very recently, cholesterol has been shown to be enriched in recycling endosome vesicles (Kawaguchi et al, 2015). The formation of double-membraned vesicles is unclear; however, we found several U-shaped single-membraned vesicles (see Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Although vesicular clustering might, at some level, be in agreement with the reduction of recycling endosome efficiency that we report here, the existence of vesicles with double membranes suggests a distinct mechanism to rearrange membranes that we have not addressed and might be related to lipid metabolism. Interestingly, very recently, cholesterol has been shown to be enriched in recycling endosome vesicles (Kawaguchi et al, 2015). The formation of double-membraned vesicles is unclear; however, we found several U-shaped single-membraned vesicles (see Fig.…”
Section: Discussionmentioning
confidence: 49%
“…This notion is in agreement with vRNPs being found at the ER 16 . Interestingly, biogenesis of viral inclusions seems to be intertwined with deregulation of the ERC, which is coherent with a decrease in recycling of transferrin during infection 14,21 , and with Rab11 detection in the ER, as if it was re-directed to this organelle during infection 16 . Whether Rab11 vesicles are targeted to the ER to deliver or to collect vRNPs will be addressed in the future.…”
Section: Discussionmentioning
confidence: 63%
“…The process is very well-described for uninfected cells, with Rab11-GTP regulating ERC transport by recruiting molecular motors, tethers and SNARES to respectively drive, dock and fuse vesicles to the plasma membrane 18 . Despite initial reports that the functional role of Rab11 was to deliver vRNPs to the cell surface 10,12,17,19 , accumulating evidence analyzing Rab11 sub-cellular localization and non-abundancy in virions 14,16,20 , binding partners 14 and host transferrin recycling 14,21 strongly indicates that Rab11 is redirected and its function is impaired during IAV infection. In fact, it was demonstrated that vRNPs outcompeted Rab11 effectors for Rab11 binding, rendering the recycling process sub-optimal 14 .…”
Section: Main Textmentioning
confidence: 97%
“…To compare formation of the putative assembly sites between dTHP1 cells and MDM, we used in situ proximity ligation assay (PLA). PLA allows for detection of two proteins localized within 40-nm distance of each other and has been used to visualize IAV assembly sites on the plasma membrane (38). In addition to measuring PLA signal between the given pair of proteins, we also co-stained cells for cell surface NA to identify infected cells.…”
Section: Resultsmentioning
confidence: 99%